Policies for Macrofinancial Stability : How to Deal with Credit Booms - Bakker, Bas (Staff Discussion Notes; Staff Discussion Notes ;, 2012)
This note explores the costs and benefits of different policy options to reduce the risks associated with credit booms, drawing upon several country experiences and the findings from econometric analysis.